Indeterminate results of interferon gamma release assays in the screening of latent tuberculosis infection: a systematic review and meta-analysis - Zhou, Guozhong; Luo, Qingyi; Luo, Shiqi; Chen, Hongbo; Cai, Shunli; Guo, Xin; He, Jian; Xia, Yuan; Li, Hanse; Zhou, Yingchen; Zhang, Yazhou; Song, Chao (Frontiers in Immunology, 2023)
Objectives: We aimed to evaluate the indeterminate rate of interferon-gamma release assays (IGRA) in detecting latent tuberculosis infection (LTBI). Methods: On 15 November 2022, we searched the PubMed, Embase, and Cochrane Library databases according to PRISMA guidelines. Two investigators independently extracted the study data and assessed its quality using a modified quality assessment of diagnostic accuracy studies (QUADAS-2) tool. A random-effects model was used to calculate pooled results. Results: We included 403 studies involving 486,886 individuals and found that the pooled indeterminate rate was 3.9% (95% confidence interval [CI]: 3.5–4.2%). The pooled indeterminate rate of QuantiFERON®-TB (QFT) was similar to that of T-SPOT®.TB (T-SPOT) (OR = 0.88 [95% CI: 0.59–1.32]); however, the indeterminate rate of a new generation of QFT (QFT-plus) was lower than that of T-SPOT (OR = 0.24 [95% CI: 0.16–0.35]). The indeterminate rate in the immunocompromised population was significantly higher than that in healthy controls (OR = 3.51 [95% CI: 2.11–5.82]), and it increased with the reduction of CD4+ cell count in HIV-positive patients. Children’s pooled indeterminate rates were significantly higher than those of adults (OR = 2.56 [95% CI: 1.79–3.57]), and the rates increased with children’s age decrease. The proportion of failed positive control in indeterminate patients was 94.6% (95% CI: 89.6–98.0%). Conclusion: On average, 1 in 26 tests yields intermediate IGRA results. QFT-plus may have the advantage of low indeterminate rate. The immunocompromised population and young children were associated with a high indeterminate rate. Additionally, failed positive control was the primary cause of most indeterminate results.